A causal interpretation of extensive and intensive margin effects in generalized tobit models - Kevin E. Staub (University of Zurich, Socioeconomic Institute, 2010)
The usual decomposition of effects in corner solution models into extensive and intensive margins is generally incompatible with a causal interpretation. This paper proposes a decomposition based on the joint distribution of potential outcomes which is meaningful in a causal sense. The difference between decompositions can be substantial and yield diametrically opposed results, as shown in a standard Tobit model example. In a generalized Tobit application exploring the effect of reducing firm entry regulation on bilateral trade flows between countries, estimates suggest that using the usual decomposition would overstate the contribution of the extensive margin by around 15%.
Keywords: C24; C34; F14; 330; limited dependent variables; potential outcomes; causality; conditional-on-positives effect; Tobit; two-part model; country margins of trade; Diskrete Entscheidung; Nutzenfunktion; Willingness to pay; Modellierung; Theorie